Bio-Bleaching of Cotton with H2O2 Generated from Native and Immobilized Glucose Oxidase. Issue 2 (March 2019) - Madhu, Amit; Chakraborty, J. N.
Enzymatically-generated hydrogen peroxide (H2 O2 ) using glucose oxidase (GOX) is a sustainable alternative for cotton textile bleaching. GOX catalyzes the oxidation of glucose to gluconic acid with generation of H2 O2 as a side product for bleaching. This work involves the study of cotton fabric bleaching with enzymatically-generated H2 O2 . Enzyme and glucose concentrations significantly affect peroxide generation as well as bleaching and were optimized using statistical experimental design in reference to maximum whiteness. Furthermore, the sustainability of this bleaching system was premeditated by GOX immobilization. GOX was covalently immobilized onto a natural and inexpensive support (chitosan) based on statistical experimental design results. The immobilization improved whitening results as well as allowing repeated application of enzyme for H2 O2 generation, which was successively implemented for cotton textile bleaching.